Synthesis and characterization of Li4Ti5O12 - Majid, Siti Rohana; Arof, Abdul Kariem; Alias, N.A.; Kufian, M.Z.; Teo, L.P. (Elsevier, 2009)
Lithium titanate, Li4Ti5O12 was prepared by the sol-gel method. The precursor was sintered at various temperatures (700, 800, 900 and 1000 degrees C) for I h and was also sintered at various times from 1 to 5 h at 800 degrees C. TGA and XRD were used to characterize the prepared samples. From TGA studies it was observed that the thermogram was no longer dependent on temperature from 600 degrees C onwards. The XRD patterns showed peaks attributable to Li4Ti5O12 phase for all prepared samples. Charge-discharge characteristics of the cells fabricated with the prepared lithium titanate were studied. (C) 2009 Elsevier B.V. All rights reserved.